(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
The advent of financial technology (Fintech) has significantly reshaped the landscape of the banking industry, introducing innovations that challenge traditional banking models. This study aims to identify and analyse the key drivers of fintech disruption and assess their impact on conventional banking institutions. Through a comprehensive literature review, this research identifies critical factors such as technological advancements, regulatory changes, customer expectations, and competitive dynamics as primary catalysts of fintech disruption. The study further investigates how these drivers influence the operational and strategic responses of traditional banks, leading to changes in service delivery, customer engagement, and business models. By examining the literature, the research highlights the adaptive strategies employed by traditional banks to remain competitive in a rapidly evolving financial ecosystem. The findings provide valuable insights for policymakers, financial institutions, and fintech companies, offering a nuanced understanding of the interplay between innovation and regulation, and paving the way for more resilient and customer-centric banking solutions.